2020
DOI: 10.1002/lio2.342
|View full text |Cite
|
Sign up to set email alerts
|

Childhood tonsillectomy alters the primary distribution of HPV‐related oropharyngeal squamous cell carcinoma

Abstract: Objectives: We investigated how tonsillectomy during childhood may influence the distribution of human papillomavirus (HPV) positive cancer of the tonsils in adult life using p16 as a surrogate marker for HPV infection.Study Design: Retrospective observational study.Methods: A total of 280 patients diagnosed with oropharyngeal squamous cell carcinoma (OPSCC) and known p16 status were eligible for this study. Each participant was called to obtain the childhood tonsillectomy history. Respondents were subgrouped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…As expected, the majority of HPV-positive OPSCC were located in the tonsils and tongue base, which is likely due to the crypt epithelium present in lymphoid tissue which provides an entry point for HPV [11]. Another potential contributor to the increased incidence of HPV-mediated tonsillar cancer is the decline in tonsillectomy rates over the past 50 years [15]. A recent study found that patients with a HPV-positive OPSCC at a non-tonsil site were much more likely to have had a previous tonsillectomy, suggesting if tonsils are present, they are a risk factor for developing primary tonsillar OPSCC [15].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As expected, the majority of HPV-positive OPSCC were located in the tonsils and tongue base, which is likely due to the crypt epithelium present in lymphoid tissue which provides an entry point for HPV [11]. Another potential contributor to the increased incidence of HPV-mediated tonsillar cancer is the decline in tonsillectomy rates over the past 50 years [15]. A recent study found that patients with a HPV-positive OPSCC at a non-tonsil site were much more likely to have had a previous tonsillectomy, suggesting if tonsils are present, they are a risk factor for developing primary tonsillar OPSCC [15].…”
Section: Discussionmentioning
confidence: 53%
“…Another potential contributor to the increased incidence of HPV-mediated tonsillar cancer is the decline in tonsillectomy rates over the past 50 years [15]. A recent study found that patients with a HPV-positive OPSCC at a non-tonsil site were much more likely to have had a previous tonsillectomy, suggesting if tonsils are present, they are a risk factor for developing primary tonsillar OPSCC [15]. In both groups, oral cavity and OPSCC were more common in males.…”
Section: Discussionmentioning
confidence: 99%
“…The higher proportion of BOT primaries among older individuals is conceivably an inverse function of childhood tonsillectomy rates, which have decreased over recent decades with changing practice patterns and surgical indications. 12,13 Prior analyses have demonstrated that the distribution of cancer among oropharyngeal subsites is modified by the absence of palatine tonsillar tissue, [14][15][16] such that childhood tonsillectomy confers a higher odds of BOT and decreased odds of tonsil subsite. Although the NCDB does not include history of tonsillectomy, extrapolation from NHANES, a representative population-based data set, suggests that odds of a BOT cancer in the NCDB (aOR = 2.9) is similar to the odds of self-reported tonsillectomy in NHANES (aOR = 3.6) for 70+ compared with <50 year olds.…”
Section: Discussionmentioning
confidence: 99%
“…Исследование Altenhofen В. показало, что среди пациентов с ВПЧ-положительным статусом рак миндалин отмечается чаще (93%), чем другая локализация рака головы и шеи (45%, р < 0,001). Результаты логистической регрессии показали, что женский пол (ОШ= 4,2, р = 0,0675), курение (ОШ = 2,6, P = 0,0367) и интактные миндалины (ОШ = 15,2, р < 0,0001) связаны с риском развития рака миндалин [55]. Таким образом, полное удаление миндалин (полная, а не частичная тонзиллэктомия) приведет к снижению заболеваемости раком миндалин, связанным с ВПЧ.…”
Section: тонзиллэктомияunclassified
“…Однако кажется сомнительным, что тотальная тонзиллэктомия повлияет на частоту развития плоскоклеточного рака головы и шеи, несвязанного с ВПЧ, и уменьшает общую частоту возникновения рака головы и шеи. По этой причине тонзиллэктомия как политика Обзор Review общественного здравоохранения для снижения ВПЧ-ассоциированного рака головы и шеи является ошибочной [55]. Кроме того, глоточные миндалины выполняют важные физиологические функции.…”
Section: тонзиллэктомияunclassified